Volvariella variicystidiosa sp. nov. (Agaricaceae, Basidiomycota) from Punjab, Pakistan - Haqnawaz, Muhammad; Khan, Zaman; Niazi, Abdul Rehman; Khalid, Abdul Nasir (Phytotaxa, 2023)
During surveys in the rainy season, a few collections of a novel Volvariella species were found on the decomposed matter, and sandy soil from the bed of the Indus River, Muzaffargarh, and Noorpur Thal, Khushab, Punjab, Pakistan. Phylogenetic analysis of the internal transcribed spacer (nrITS) has confirmed that this new species (namely Volvariella variicystidiosa) forms a separate clade from the previously known species of Volvariella. Volvariella variicystidiosa differs from a closely related species, V. taylorii, by its dull brown umbo and grayish brown striations on the pileus toward the margins, dull orange lamellae, and anatomically light yellow to gray pileipellis. Our new taxon is also different from existing species by having cheilocystidia and pleurocystidia with a broad variation of shapes and sizes. Abundant cheilocystidia are cymbiform to mucronate, narrowly to broadly moniliform with a broad base, and rarely broadly ellipsoid to ellipsoid with obtuse apex, triangular to conical; pleurocystidia are moderately ellipsoid, rarely flexuous and oblong. Our findings provide evidence that this fungus represents a new taxon and it is a great addition to our current knowledge of the vast diversity of Volvariella species.